Low-dimensional halide perovskite/PVDF nanocomposite with enhanced piezoelectricity as flexible biomechanical energy harvester - Nisha Hiralal Makani; Prabhat Kumar; Tufan Paul; Aditi Sahoo; Soumen Maiti; Rupak Banerjee (Chemical Physics Impact, 2024)
Sustainable energy harvesting is the need of the hour, and piezoelectric nanogenerators (PENG) offer tremendous opportunities in this field. We have investigated the mechanical energy harvesting applications of a nanocomposite comprising a low-dimensional halide perovskite (HP) and polyvinylidene fluoride (PVDF). Cs4PbBr6 HP was prepared using mechanochemical synthesis, and a composite film of PVDF with Cs4PbBr6 was utilized as the PENG to scavenge energy from day-to-day human biomechanical activities. The properties and output results of the fabricated devices with changing weight percentages (wt.%) of HP used as nanofillers in the PVDF matrix are compared to those of a pure PVDF. A 6 wt.% concentration of Cs4PbBr6 induces the composite's electroactive β-phase to around 87%. The polarization hysteresis (P-E) loop measurement reveals a remanent polarization of 0.31 µC/cm2. The measured piezoelectric coefficient (d33) is about ⁓12 pm/V, and the piezoelectric amplitude is ∼500 pm for the optimized PENG at the maximum applied bias of ±30 V. The device shows an instantaneous output voltage of ⁓90 V, a current of ⁓3.8 μA, and power of ⁓80 µW across a 5 MΩ resistor. Simple daily human activities like finger tapping, leg-toe pressing, finger bending, heel pressing, and walking are used to generate output voltages using PENG with prospective usage in powering portable electronic devices. The output AC voltage of the device is employed to charge a 10 µF capacitor up to ∼3.5 V and shows exceptional stability over long cycles. The output power generated is adequate for lighting commercial LEDs without any external input. The Cs4PbBr6/PVDF composite films thus demonstrate significant potential to be deployed as high-performance, portable, and wearable mechanical energy harvesting devices.